Colorectal Cancer Screening in Switzerland: Cross-Sectional Trends (2007-2012) in Socioeconomic Disparities. - Stacey A Fedewa (PLoS ONE, 2015)
Despite universal health care coverage, disparities in colorectal cancer (CRC) screening by income in Switzerland have been reported. However, it is not known if these disparities have changed over time. This study examines the association between socioeconomic position and CRC screening in Switzerland between 2007 and 2012.Data from the 2007 (n = 5,946) and 2012 (n = 7,224) population-based Swiss Health Interview Survey data (SHIS) were used to evaluate the association between monthly household income, education, and employment with CRC screening, defined as endoscopy in the past 10 years or fecal occult blood test (FOBT) in the past 2 years. Multivariable Poisson regression was used to estimate prevalence ratios (PR) and 95% Confidence Intervals (CI) adjusting for demographics, health status, and health utilization.CRC screening increased from 18.9% in 2007 to 22.2% in 2012 (padjusted: = 0.036). During the corresponding time period, endoscopy increased (8.2% vs. 15.0%, padjusted:<0.001) and FOBT decreased (13.0% vs. 9.8%, padjusted:0.002). CRC screening prevalence was greater in the highest income (>$6,000) vs. lowest income (≤$2,000) group in 2007 (24.5% vs. 10.5%, PR:1.37, 95%CI: 0.96-1.96) and in 2012 (28.6% vs. 16.0%, PR:1.45, 95%CI: 1.09-1.92); this disparity did not significantly change over time.While CRC screening prevalence in Switzerland increased from 2007 to 2012, CRC screening coverage remains low and disparities in CRC screening by income persisted over time. These findings highlight the need for increased access to CRC screening as well as enhanced awareness of the benefits of CRC screening in the Swiss population, particularly among low-income residents.